TGFβ1 Controls PPARγ Expression, Transcriptional Potential, and Activity, in Part, through Smad3 Signaling in Murine Lung Fibroblasts - Allan Ramirez; Erin N. Ballard; Jesse Roman (PPAR Research)
Transforming growth factor β1 (TGFβ1) promotes fibrosis by, among other mechanisms, activating quiescent fibroblasts into myofibroblasts and increasing the expression of extracellular matrices. Recent work suggests that peroxisome proliferator-activated receptor γ (PPARγ) is a negative regulator of TGFβ1-induced fibrotic events. We, however, hypothesized that antifibrotic pathways mediated by PPARγ are influenced by TGFβ1, causing an imbalance towards fibrogenesis. Consistent with this, primary murine primary lung fibroblasts responded to TGFβ1 with a sustained downregulation of PPARγ transcripts. This effect was dampened in lung fibroblasts deficient in Smad3, a transcription factor that mediates many of the effects of TGFβ1. Paradoxically, TGFβ1 stimulated the activation of the PPARγ gene promoter and induced the phosphorylation of PPARγ in primary lung fibroblasts. The ability of TGFβ1 to modulate the transcriptional activity of PPARγ was then tested in NIH/3T3 fibroblasts containing a PPARγ-responsive luciferase reporter. In these cells, stimulation of TGFβ1 signals with a constitutively active TGFβ1 receptor transgene blunted PPARγ-dependent reporter expression induced by troglitazone, a PPARγ activator. Overexpression of PPARγ prevented TGFβ1 repression of troglitazone-induced PPARγ-dependent gene transcription, whereas coexpression of PPARγ and Smad3 transgenes recapitulated the TGFβ1 effects. We conclude that modulation of PPARγ is controlled by TGFβ1, in part through Smad3 signals, involving regulation of PPARγ expression and transcriptional potential.